Using Pomegranate Peel Extract to Change the Adverse Effect of Ethephon by Enhancing its Antioxidant, Anti-inflammatory, and Anti-apoptotic Effects in Rats (Baghdad Science Journal, 2022)
Organophosphorus insecticide and growth regulator namely Ethephon (2-chloroethylphosphonic acid) are widely used as a ripening process accelerator and a cultivation duration inhibitor. Pomegranate extract (PPE) has recently been taken into consideration due to its pharmacological effects especially those associated with renal diseases. Thus, this study aims to investigate the possible protective effect of PPE against ethephon-induced nephrotoxicity in rats. In this study four groups of adult male rats were divided into control group, PPE 400 mg/kg group, Ethephon 250 mg/kg group, and finally, PPE + Ethephon group (treated with the same dose of PPE group and Ethephon group). In the current study, kidney function parameters (KIM-1, creatinine, and urea) along with oxidative stress markers, heme oxygenase-1 (HO-1) and nuclear factor erythroid 2–related factor 2 (Nrf2), glutathione (GSH) and its correlated enzymes, nitric oxide (NO), superoxide dismutase (SOD), malondialdehyde (MDA) and catalase (CAT) were estimated. Additionally, mediators of renal inflammation: interleukin 1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B (NF-κB) were measured. Apoptotic biomarkers (Bax, caspase 3, and Bcl2) in addition to renal histopathological data were also investigated. Results revealed that Ethephon elicited a significant increase in oxidation markers and reduced antioxidant levels, accompanied by oxidative renal tissue injury. Consequently, administration of Ethephon was reported to provoke secretion of the pro-inflammatory mediators. Moreover, histopathological results showed that deformities in the renal tissues were noticed which is attributed to Ethephon exposure. Interestingly, co-administration of PPE and Ethephon resulted in significantly ameliorated the biochemical and histopathological alterations produced by Ethephon. Current results propose the potential effect of PPE in the protection of renal tissue from Ethephon induced nephrotoxicity in rats.